Differential optimal dopamine levels for set-shifting and working memory in Parkinson's disease. (October 2015) - Fallon, Sean James; Smulders, Katrijn; Esselink, Rianne A.; van de Warrenburg, Bart P.; Bloem, Bastiaan R.; Cools, Roshan
Abstract: Parkinson's disease (PD) is an important model for the role of dopamine in supporting human cognition. However, despite the uniformity of midbrain dopamine depletion only some patients experience cognitive impairment. The neurocognitive mechanisms of this heterogeneity remain unclear. A genetic polymorphism in the catechol O- methyltransferase (COMT) enzyme, predominantly thought to exert its cognitive effect through acting on prefrontal cortex (PFC) dopamine transmission, provides us with an experimental window onto dopamine's role in cognitive performance in PD. In a large cohort of PD patients ( n =372), we examined the association between COMT genotype and two tasks known to implicate prefrontal dopamine (spatial working memory and attentional set-shifting) and on a task less sensitive to prefrontal dopamine (paired associates learning). Consistent with the known neuroanatomical locus of its effects, differences between the COMT genotype groups were observed on dopamine-dependant tasks, but not the paired associates learning task. However, COMT genotype had differential effects on the two prefrontal dopamine tasks. Putative prefrontal dopamine levels influenced spatial working memory in an 'Inverted-U'-shaped fashion, whereas a linear, dose-dependant pattern was observed for attentional set-shifting. Cumulatively, these results revise our understanding of when COMT genotype modulates cognitive functioning in PD patients by showing that the behavioural consequences of genetic variation vary according to task demands, presumably because set-shifting and working memory have different optimal dopamine levels. Highlights: Parkinson's disease (PD) is an important model for the role of dopamine in cognition. Not all patients are impaired on tasks that depend upon dopamine levels. Genetic variations in COMT that affect dopamine levels may explain this heterogeneity. These genetic variations had different effects on set-shifting and working memory. Optimal dopamine levels required for set-shifting and working memory may be different.